PERANCANGAN MOTIF BATIK EKSPRESIONISME ABSTRAK DENGAN SUMBER IDE SISI EMOSIONAL UNTUK FASHION STYLE BAD GIRL - Shafira Nabila; Mursidah; Yustiana Dwirainaningsih (Akademi Seni dan Desain Indonesia Surakarta, 2024)
The most young people didn’t like batik that seems old-fashioned with colors that seems monotonous. This design is a from of innovation to foster like and interest for young people so that batik willn’t be immersed in foreign cultures and will countinue to exist in the future. This design is an innovation that develops abstract contemporary batik with more expressionism in which the depiction displays the emosional side experienced by female figure who became the ideas for this work. In terms of images that are randomly generaled with the appearance of expressions human. In addition, the color ascept is made to show the emosional side. Observation of motifs and colors is done through the media of the books and the internet. This batik is realize using the written batik technique, with the coloring using the dab technique. This batik work is packaged or realized in the form of Bad Girls Style which reflects the figure of feminine girl who became a new, tomboyish personality. The results of this design trial obtained 3 motifs with 7 fashion designs which are illustrated in the from of 3 motifs in 1 design and realized with the chosen motif, namely the Confundo motif on a bad girl outfit. Keyword : Bad Girl, Contemporary Batik, Ekspresionism